Establishment of the wasp Tetramesa romana for biological control of Arundo donax in northern California and the role of release plot manipulation - Ellyn V. Bitume; D. Valle Rogers; Paul D. Pratt; John A. Goolsby; Patrick J. Moran (Biological Control)
Arundo donax is a non-native, invasive large-statured grass of riparian systems in the southwestern USA, including the Sacramento and San Joaquin River watersheds of northern California and the Sacramento-San Joaquin Delta. In 2017, the shoot tip-galling wasp Tetramesa romana was released at nine sites, three in each region. Shoots in some release plots were manipulated prior to release by cutting to ground or pruning to 1 m height, while others were left uncut. One year later, exit holes made by emerging adult wasps were found at two of nine sites. Exit hole density per main shoot length was 16-fold higher on regrowth shoots in ground-cut plots than in uncut plots. An additional plot manipulation study at two other sites found that exit hole density per shoot length was 19-fold higher in plots that were double-cut (cut to ground and regrowth pruned) than in single-cut plots. By 2023, T. romana was established at eight sites spanning both river watersheds and their Delta with dispersal up to 6.5 km, based on dissection of shoots, multi-year counts of exit holes and galls, and trapping of adult T. romana with sticky traps. The abundance of T. romana may be limited in northern California by low annual heat unit accumulation. The results show that physical manipulation of host plants improves short-term establishment and demonstrate the importance of using multiple monitoring methods to determine long-term establishment.